IMPLEMENTASI TAJDIDUN NIKAH PADA MASYARAKAT MADURA (STUDI KASUS DI KUA KECAMATAN AMBUNTEN) - Syaiful Hidayat; Khoirul Asfiyak; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Astrack: Marriage is a contract or bond to justify the sexual relations between men and women in order to realize happiness in a family life that is overwhelmed with a sense of peace and compassion in a way diridhai Allah SWT. With the onset of the marriage contract a connection between a man and woman is legally established and on each shoulder lies responsibility that must be carried out honestly, Islam gives instructions and various provisions to the husband as the head of the family regarding his obligations that must be fulfilled and in responsible. This study uses a qualitative descriptive qualitative approach, namely a study that describes and describes a problem. The researcher tried to explain and describe the implementation of Tajdidun Nikah in Tamba Agung Timur Village, Ambunten District, Sumenep Regency. This type of research is a case study or field study. Case research is an in-depth study of a particular unit, the results of which research provides a broad and in-depth description of a particular unit. Look at and see the fact that the texts (Al-Qur'an and Hadith) are relatively limited while the problems that arise in the community are relatively unlimited even tend to be complex and complicated, then look for special texts (direct text) to solve all problems directly (one by one) ), both to require, forbid, or justify, will feel illogical and unworthy and are considered burdensome with something heavy and even impossible. Changes that occur in the community now, if compared to the situation in the past have been very different, mainly because there is a paradigm shift, so it is necessary to form a method that is in accordance with the new paradigm currently in use. Based on the results of the research and discussion can be summarized as follows: First, the results of the study show that there are two categories of causes of repeated marriage. First, it is caused by lack of harmony and the legal requirements for a marriage. In the Case of Finding a Good Date, Guardian Nasab, and in the case of Separate Beds. A legitimate marriage is a marriage that fulfills all pillars and conditions. Conversely, a marriage that does not fulfill harmony and conditions, the marriage is not valid. Secondly, it was caused by wanting to complete the Population Administration. Marriage repetition that occurred in KUA Ambunten Sub-district was carried out because it would cause benefits for married couples, if the marriage repetition did not occur then the harm would arise, and would have a negative effect on both partners.